Efficiency of ultrasound-guided placental gene therapy in a rabbit IUGR model and effects on offspring development - Trigo, María Soledad; Gonzalez-Bulnes, Antonio; García-Rebollar, Pilar; Formoso-Rafferty, Nora; Cejalvo, Teresa; García-Castro, Javier; Yeste-Vizcaíno, Natalia; Barbero-Fernández, Alicia (Frontiers in Veterinary Science, 2025)
Placental insufficiency is a major cause of intrauterine growth restriction (IUGR), and no effective prenatal therapy is currently available. Previous studies have demonstrated that gene therapies based on overexpression of insulin-like growth factor 1 (IGF-1) and vascular endothelial growth factor (VEGF) can improve prenatal and postnatal development. Such therapies are mostly adenovirus-mediated, since adenoviral vectors are the most widely used vehicles for gene delivery due to their broad cellular tropism, ability to transduce non-dividing cells, and relative easiness of production and titration. Hence, this study evaluated the feasibility and safety of a novel minimally invasive ultrasound-guided intraplacental technique for the injection of adenoviral vectors encoding IGF-1 or VEGF in a rabbit model of IUGR, in which the condition was induced by maternal feed restriction to 50% of the average daily intake during gestation. Postnatal development was assessed through biometric measurements (body weight), metabolic profiling (lipid, carbohydrate, and protein metabolism), and histological cell counts in key organs. The results confirmed the marker expression by adenoviral vectors in all the treated fetuses and the absence of deleterious effects of the ultrasound-guided injection on the postnatal survival and growth of the offspring. The use of the technique for inducing both IGF-1 and VEGF over-expression by administration of adenoviral vectors in an IUGR model showed, in the case of VEGF, positive effects on the developmental and metabolic traits, with especial significance in the pulmonary and intestinal systems, of IUGR offspring. Hence, after further research, the proposed therapy may offer potential benefits in pregnancies with placental insufficiency and IUGR conditions.